VALUES IN THE EXPRESSION OF THE PEOPLE OF MALANG REGENCY: NILAI-NILAI DALAM UNGKAPAN RAKYAT MASYARAKAT KABUPATEN MALANG - Anggita Elma Vira; Eggy Fajar Andalas (LLDIKTI Wilayah X, 2022)
Oral literature becomes a tools of learning and teaching behavior of the owner community. People believe that expressions can turn bad into good, and reject calamities that are conveyed through the form of prohibitions, orders, or simply giving fear to perpetrators of norm deviation. This study aims to describe the educational values contained in oral literature. This research was conducted with a descriptive-qualitative method. The data source of this research is the people of Cerme Hamlet, Kendalpayak Village, Pakisaji District, Malang Regency. The data were collected using observation, interview, and document study techniques. Data analysis was performed by presenting data, reducing data, and drawing conclusions. The results showed that there were 13 expressions, each of which contained useful values for life. These values consist of educational values, social values, and religious values.